2015
DOI: 10.21307/sjcapp-2016-010
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety Disorders among Adolescents referred to General Psychiatry for Multiple Causes: Clinical Presentation, Prevalence, and Comorbidity

Abstract: Background: Reports of anxiety disorder characteristics among youth in clinical settings typically include descriptions of patients who have been specifically referred for anxiety treatment. At odds with a large body of evidence which demonstrates these disorders to be most common among young people, prevalence studies in samples referred to general psychiatry for multiple causes are scarce and report highly discrepant estimates. Methods: For this study and regardless of their presenting symptoms, 125 adolesce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…It was shown that internalizing disorders, such as depression, anxiety, and somatic symptoms, were seen more commonly in girls than boys in many studies, similar to our study. [14] Olofsdotter et al [10] reported that girls had three times more anxiety disorders than boys. In another study, disruptive behavior disorders were found to be three times more common in boys than in girls.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It was shown that internalizing disorders, such as depression, anxiety, and somatic symptoms, were seen more commonly in girls than boys in many studies, similar to our study. [14] Olofsdotter et al [10] reported that girls had three times more anxiety disorders than boys. In another study, disruptive behavior disorders were found to be three times more common in boys than in girls.…”
Section: Discussionmentioning
confidence: 99%
“…[8] Apart from NDD, the most common psychiatric diagnoses in children and adolescents are disruptive behavior disorders, such as oppositional defiant disorder and conduct disorder and internalizing disorders, such as anxiety disorder and depression. [9][10][11] Previous studies have investigated the risk factors of non-neurodevelopmental psychiatric disorders (NNDD), which represent internalizing and/or externalizing disorders. Studies have shown that low socioeconomic level, maternal anxiety disorder, and female gender are risk factors for internalizing disorders.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Symptoms of MDD are one of the most common reasons for help-seeking among adolescents in child and adolescent psychiatric services [1]. In the community-based adolescent population, the lifetime-and 12-month prevalence of major depression disorder (MDD) is 11% and 7.5% respectively [2].…”
Section: Introductionmentioning
confidence: 99%